Between reciprocity and agrarian transformation: Challenges to land tenancy and labor relations among rice-farming communities in Lahat Regency, South Sumatra Province, Indonesia - Widiono, Septri; Melia, Jheni Juwita Sari; Sukiyono, Ketut; Serawai, Bembi Akbar (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2025)
Land tenancy and labor relations are two agrarian institutions that shape the organization of agricultural activities at the production level and often influence production performance. This study explores the patterns of land tenancy and labor relations among rice-farming communities in Lahat Regency, South Sumatra, through the lens of the reciprocity economic perspective. Employing a qualitative case study approach, the research was conducted in four villages across the sub-districts of Tanjung Sakti Pumi and Lahat Selatan. Data were collected through in-depth interviews with the tenant farmers, landowners, extension officers, and community leaders. Findings reveal two dominant sharecropping systems: an equal 1:1 distribution and a saseh system with a 2:1 share. These informal and unwritten arrangements are based on kinship ties, mutual trust, and local norms. They provide stable land access for landless farmers and maintain production continuity, despite limited institutional support. Labor relations are equally embedded in cultural practices such as gotong royong (mutual aid), where families and neighbors contribute unpaid or semi-paid labor during peak agricultural periods. Compensation may include food, rice, or low wages, depending on the relationship and labor type. However, they reveal underlying tensions between tradition and social transformation, in which evolving reciprocity practices may increasingly function as mechanisms of surplus accumulation under market penetration. Theoretically, this study contributes to rural sociology by demonstrating how informal systems of tenancy and labor persist as rational and adaptive responses to socio-economic constraints, while also highlighting their potential vulnerability to erosion under agrarian pressures. The findings suggest that development policies should aim to reinforce these community-based systems to improve agricultural sustainability and social equity in rural Indonesia.